Pengaruh Rasio Keuangan Terhadap Return Saham Pada Industri Semen di Indonesia - Hananda Priyandaru (Universitas Bina Sarana Informatika, 2019)
This study aimed to examine the effect of financial ratios on stock returns, either individually per variable or effect simultaneously. This study is causal comparative, by knowing the relationship and the influence of independent variables on the dependent variable. The object of this research is in Indonesian cement companies that has already go public.This research is based on the fact that the secondary data obtained from the Jakarta Stock Exchange during the five years, namely 2009, 2010, 2011, 2012 and 2013. The data analysis was conducted using pooled cross-section time series, with eviews 8 program. Result of hypothesis examination showed that of the six hypotheses proposed, assuming a confidence level (α = 5%), there is an accepted hypothesis and assumptions are used when the confidence level (α = 10%), there are two hypotheses are accepted. At the 5% level of confidence accepted hypothesis is the hypothesis 2 (there is influence between solvency ratio on stock returns). At the 10% confidence level accepted hypothesis is the hypothesis 2 (there is influence between solvency ratio on stock returns) and hypothesis 3 (there is the influence of the ratio of activity on stock returns). Furthermore, with a confidence level (α = 5%), then the hypothesis is rejected hypothesis 1, hypothesis 3, hypothesis 4, hypothesis 5 and hypothesis 6.